1991
DOI: 10.1007/bf01314029
|View full text |Cite
|
Sign up to set email alerts
|

An unusual transmissible agent ? MaTu

Abstract: MaTu is an agent, believed to be derived from a human mammary carcinoma, which displayed several extraordinary properties. These were: RIP and PAGE revealed in MaTu-infected cells only a single protein band of Mr 58 k, the gp 58. This gp 58 was immunoprecipitated by antibodies present in some human sera as well as in some sera of rabbits, sheep, and cattle. MaTu had an extremely restricted host range: it was transmissible only to HeLa cells, but not to human embryo fibroblasts, to three human tumour cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…It has already been proven that lymphocytic choriomeningitis virus can establish long-term non-cytolytic infection in vitro and spread in culture by cell-to-cell contacts (Zavada and Zavadova, 1991). As demonstrated using the LCMV strain MX, during persistent infection, the viral particles are not released to medium, so the uninfected cells could not be infected by the regular virus-receptor interaction.…”
Section: Cell-to-cell Transmissionmentioning
confidence: 94%
“…It has already been proven that lymphocytic choriomeningitis virus can establish long-term non-cytolytic infection in vitro and spread in culture by cell-to-cell contacts (Zavada and Zavadova, 1991). As demonstrated using the LCMV strain MX, during persistent infection, the viral particles are not released to medium, so the uninfected cells could not be infected by the regular virus-receptor interaction.…”
Section: Cell-to-cell Transmissionmentioning
confidence: 94%
“…It was identified as the transmembrane carbonic anhydrase isoform IX (CAIX) (Opavsky et al, 1996;Pastorek et al, 1994), the expression of which is predominantly associated with hypoxic tumors of poor prognosis (Wykoff et al, 2000). Previous evidence suggested that LCMV MX might induce the expression of CA IX (Zavada and Zavadova, 1991). If this were true then the virus infection would represent a potential risk factor for patients with tumors.…”
Section: Lcmv MX Strain and Our Contribution To The Knowledge Of Lcmvmentioning
confidence: 97%
“…It has an extremely restricted host range and is transmissible to HeLa and HEF cells, but not to various human tumor cell lines or animal cell cultures. Notably, some human and animal sera contained antibodies that precipitated from MaTu cell extract, a single protein of 58 kDa (Zavada and Zavadova, 1991).…”
Section: Lcmv MX Strain and Our Contribution To The Knowledge Of Lcmvmentioning
confidence: 99%
“…Human MaTu cells (as described in [12]) and uninfected and LCMV MX-infected cervical carcinoma HeLa cells were cultivated in Dulbecco's Minimal Essential Medium (BioWhittaker, Verviers, Belgium) supplemented with 10% fetal calf serum and 40 lg/ml gentamicin (Lek, Slovenia) in a humidified atmosphere with 5% CO 2 at 37°C.…”
Section: Cell Lines and Virusmentioning
confidence: 99%
“…MX was initially considered an unusual transmissible agent of human carcinoma MaTu cells [12,13]. However, we have shown that this agent is in fact persisting LCMV.…”
Section: Introductionmentioning
confidence: 98%